Looking for evidence of deep learning in constructively aligned online discussions - Brown, Norrie; Smyth, Keith; Mainka, Christina (Proceedings of the International Conference on Networked Learning, 2006)
Building upon previous work by the authors, this paper describes a small-scale study that involved analysing the depth of thinking evident within asynchronous discussion contributions. The discussion tasks in question, which were undertaken within the context of a fully online distance course, were designed according to the principles of constructive alignment, and analysed using the SOLO taxonomy. Of particular interest within this study was whether the SOLO taxonomy would provide evidence of surface-to-deep or deep-to-deeper learning having occurred on an individual basis over time, and also how suitable the SOLO taxonomy was as a tool for the content analysis of online discussions. Findings on both counts were encouraging, but not unproblematic.